Chlamydia Persistence: A Survival Strategy to Evade Antimicrobial Effects in-vitro and in-vivo - Panzetta, Maria Emilia; Valdivia, Raphael H.; Saka, Hector Alex (Frontiers in Microbiology, 2018)
The Chlamydiaceae comprise a group of highly adapted bacterial pathogens sharing a unique intracellular lifestyle. Three Chlamydia species are pathogenic to humans: Chlamydia trachomatis, C. pneumoniae and C. psittaci. C. trachomatis is the leading bacterial cause of sexually-transmitted infections and infectious blindness worldwide. C. pneumoniae is a major cause of community-acquired atypical pneumonia. C. psittaci primarily affects psittacine birds and can be transmitted to humans causing psittacosis, a potentially fatal form of pneumonia. As opposed to other bacterial pathogens, the spread of clinically relevant antimicrobial resistance genes does not seem to be a major problem for the treatment of Chlamydia infections. However, when exposed to stressing conditions, like those arising from exposure to antimicrobial stimuli, these bacteria undergo a temporary interruption in their replication cycle and enter a viable but non-cultivable state known as “persistence”. When the stressing conditions are removed, Chlamydia resumes replication and generation of infectious particles. This review gives an overview of the different survival strategies used by Chlamydia to evade the deleterious effects of penicillin and IFNgamma, with a focus on the different models used to study Chlamydia persistence, their contribution to elucidating the molecular basis of this complex phenomenon and their potential implications for studies in animal models of infection.